(x-4)(x-9)=0

Simple and best practice solution for (x-4)(x-9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4)(x-9)=0 equation:


Simplifying
(x + -4)(x + -9) = 0

Reorder the terms:
(-4 + x)(x + -9) = 0

Reorder the terms:
(-4 + x)(-9 + x) = 0

Multiply (-4 + x) * (-9 + x)
(-4(-9 + x) + x(-9 + x)) = 0
((-9 * -4 + x * -4) + x(-9 + x)) = 0
((36 + -4x) + x(-9 + x)) = 0
(36 + -4x + (-9 * x + x * x)) = 0
(36 + -4x + (-9x + x2)) = 0

Combine like terms: -4x + -9x = -13x
(36 + -13x + x2) = 0

Solving
36 + -13x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(4 + -1x)(9 + -1x) = 0

Subproblem 1

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Subproblem 2

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Solution

x = {4, 9}

See similar equations:

| 3x+7=4x-16 | | 7b+6b= | | 4x-5/8+x=4x+5/4+4 | | X+39(x+25)=180 | | AE=3600-0.8Y | | 5x-3(6-x)=54 | | x+(7/10)=(-1/5) | | 4x-7/8+x=4x+7/4+1 | | 5x-3(6-z)=54 | | 0.3x-3=1.1x-15 | | 5n+9=3n+17 | | 30+2x=4(5x-2) | | 7+3/5(10+35x) | | 1.8(2.57143)+1.5b=3.3 | | 5(2/18)+8d=(-10) | | -1/4=x-2/3 | | n-5/8+n+4/9=19/36 | | 6x+2y=30 | | X^2-10x-128=0 | | -[5z-(15z+1)]=1+(9z+8) | | (y^2)+3y-5=175 | | -2x-4(6.4)=20 | | 5ln(x-1)=10 | | (4x^2+16x-21)/(2x-1) | | 7(x-3)=(x-2) | | -9(3a-4)= | | x-7=-3x-7 | | 4b(6-5b)= | | -5(3n+5)=2 | | x-27=8x+57 | | 11-7x=3-8x | | 7(8+3h)= |

Equations solver categories